Helping Ingredients (excipient) in Pharmaceutical formulation: Coloring Agents – use and health concern - Khanal, Dharma Prasad (Journal of Manmohan Memorial Institute of Health Sciences, 2014)
DOI: http://dx.doi.org/10.3126/jmmihs.v1i1.9900 Journal of Manmohan Memorial Institute of Health Sciences Vol.1(1) 2011; 40-48